Kultura instant: paradoksy pop-tożsamości = Instant culture. The paradoxes of pop-identity - Melosik, Zbyszko (1956- ) (Zielona Góra: Uniwersytet Zielonogórski)
The author touches up on the problem of (re)constructing the identity of contemporary teenagers, taking in to consideration the influence of the globalization processes and popularculture. The image of a global teenager constitutes, in this context, "crystallization" of the ofthe cultural trends that emerge, especially abolition of the "local" factors (including nationhood and statehood), in defining the answer to the question "Who am I?" The last part of the article provides an analysis of pedagogical "capabilities" and "limitations"- in the face of the confrontation of traditional educational ideais with global pop-cultural identity. The author advocates giving up the attempts at "imposed" shaping of identity, he promotes pedagogy "open" to new meanings and values accepted by teenagers.
Keywords: kultura; socjologia